Regulation and performance: A production frontier estimate for the Latin American water and sanitation sector - Ferro, Gustavo Adolfo (2011)
The objective of this paper is to analyze the efficiency of the water sector in Latin American countries. We try to find factors affecting efficiency rather than identifying which country or individual provider is more or less efficient. We also consider which model would be more fitting for the water sector production in this region. Our motivation is to develop instruments to make benchmarking operative for regulatory actions that can reduce information asymmetry and increase efficiency in Latin American countries. We estimate econometric efficiency frontiers using data from a regional survey conducted by the Latin American Association of Water Regulators. The paper develops a model based on the core variables that explain the phenomena and explores “environmental” (contextual or beyond management control) variables to achieve fair comparisons. The study does not “name and shame” services but provides elements to foster the development of indicative goals at the regional level.